Ice Fun and Winter Joy: An Interdisciplinary Study Tour Practice on Border Snow and Ice for Junior High School Students - Weixin Liu; Dandan Zhang; Siwen Liu; Guifeng Shen; Ming Gao (Education Research on Study Tours and Practice, 2026)
The border areas of Heilongjiang Province possess distinctive resources such as boundary lakes, snow and ice, and Sushen fishing-hunting culture. However, border study tours generally suffer from superficial sightseeing, disciplinary fragmentation, and vague stage-specific design, with most activities remaining at the level of landmark check-ins, failing to fully tap into their educational value. Mishan Blue Sky Experimental School, located on the China-Russia border, has leveraged local resources such as Xingkai Lake to create an interdisciplinary study tour system called “Ice Fun and Winter Joy.” Based on junior high school curriculum standards, the school has implemented practices from five aspects: institutional support, collaborative lesson preparation, three-dimensional curriculum, linkage of internal and external resources, and diversified evaluation. Using Xingkai Lake as an immersive study base, the school transforms static border and ice-snow resources into dynamic practical classrooms. This paper systematically elaborates on the design concepts, implementation paths, and educational outcomes of this curriculum system, providing a replicable practical sample for border junior high schools to develop interdisciplinary snow-and-ice study tour curricula.